Hematolymphoid tumours diagnosed at department of pathology, Sir Salimullah Medical College during two years study period - Hossain, Md Delwar; Islam, Md Nasimul; Razzak, Monira; Kamal, Mohammed; Kabir, Alamgir; Kabir, Enamul (Journal of Paediatric Surgeons of Bangladesh, 2018)
During the past century, cancer has emerged as the most challenging problems for public health systems in medium and low income source countries. With a cancer load of more than one million, Bangladesh is not an exception. The present study shows that hematolymphoid tumours (leukaemia and lymphoma) arethe third most common malignant tumours and lower income generating group is the more vulnerable group for these malignant tumours. It also shows that leukaemia is the fifth highest andlymphoma is the sixth highestof the studied malignant tumours.The most common leukaemia is acute lymphoblastic leukaemia and found in both paediatric and adult age group. Acute leukaemia is found more than chronic leukaemia and lymphoblastic and myeloblastic leukaemia are found in equal proportion. Chronic myeloid type is found more than lymphocytic type. Hodgkin lymphoma is nil in paediatric age group and more common in adult male than adult female. Non Hodgkin lymphoma is found more in adult age group and more common in male than female but in paediatric age group more common in female than male. Non Hodgkin lymphoma is found in 88% and Hodgkin lymphoma in rest 12% of the Lymphoma cases. Journal of Paediatric Surgeons of Bangladesh (2016) Vol. 7 (1): 15-19